1997
DOI: 10.1177/074873049701200106
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Circadian Rhythms during the Menstrual Cycle and Sleep Deprivation in Premenstrual Dysphoric Disorder and Normal Comparison Subjects

Abstract: The aim of this study was to test the hypothesis that the circadian rhythm of core body temperature is altered in premenstrual dysphoric disorder (PMDD) subjects compared to that in normal comparison (NC) subjects and that it is normalized in PMDD subjects after treatment with early night partial sleep deprivation (ESD) or late night partial sleep deprivation (LSD). A total of 23 subjects meeting DSM-IV criteria for PMDD and 18 NC subjects had 24-h core body temperature recordings taken during the following co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 35 publications
6
25
0
Order By: Relevance
“…In summary, we have found changes in sleep EEG during the menstrual cycle (in stage 3 sleep and number of intermittent awakenings) and that PMDD patients have more stage 2 sleep and less REM sleep (Parry et al 1989b). Temperature minima tend to be earlier and amplitude higher in PMDD vs. NC subjects (Parry et al 1989b(Parry et al , 1994(Parry et al , 1997b. Compared with NC subjects, PMDD patients have an earlier offset time, a shorter duration and a decreased area under the curve of plasma nocturnal melatonin secretion ).…”
Section: Premenstrual Dysphoric Disordermentioning
confidence: 72%
“…In summary, we have found changes in sleep EEG during the menstrual cycle (in stage 3 sleep and number of intermittent awakenings) and that PMDD patients have more stage 2 sleep and less REM sleep (Parry et al 1989b). Temperature minima tend to be earlier and amplitude higher in PMDD vs. NC subjects (Parry et al 1989b(Parry et al , 1994(Parry et al , 1997b. Compared with NC subjects, PMDD patients have an earlier offset time, a shorter duration and a decreased area under the curve of plasma nocturnal melatonin secretion ).…”
Section: Premenstrual Dysphoric Disordermentioning
confidence: 72%
“…Most [16][17][18][19][20][21][22][23], but not all [24,25], of these studies showed disturbed circadian temperature rhythms in patients with depression and other mood disorders [26,27]. Some [22,[28][29][30], but not all [31], studies on depressed patients have documented high nocturnal temperatures and higher mean 24-hour temperatures [28].…”
Section: Introductionmentioning
confidence: 99%
“…Further research is needed to identify the mechanism(s) by which reproductive hormones regulate melatonin circadian rhythms. The abnormal melatonin profiles that characterize DW during different reproductive epochs 8,18,26,47 implicate reproductive hormones in circadian rhythm dysregulation and depression. In particular, the differing reproductive hormonal milieus that characterize each reproductive epoch (menstrual cycle, pregnancy, postpartum, and menopause) have distinguishable melatonin profiles associated with each depressive state.…”
Section: Implications For Treatment and Researchmentioning
confidence: 99%
“…For example, phase-advanced and low melatonin quantities characterize PMDD and pregnant DW, whereas phasedelayed and increased melatonin AUC characterize postpartum and menopausal depression. 8,18,26,47 Understanding the relationship of reproductive hormones to circadian rhythm dysregulation may elucidate important mechanisms in women's depressions.…”
Section: Implications For Treatment and Researchmentioning
confidence: 99%